PELAKSANAAN SANKSI ADAT BAGI PELAKU ZINA DI KECAMATAN SELUMA UTARA KABUPATEN SELUMA PERSPEKTIF HUKUM ISLAM - Suparlan, Elon (UIN Fatmawati Sukarno Bengkulu, 2018)
This study discusses the implementation of the determination of Integrated Marriage of The formulation of this research are: Firstly, how is the society’s response to the enactment of Government Regulation No. 19 of 2015 on Non-Tax State Revenue in the Ministry of Religious Affairs? Second, what factors cause the community to carry out marriage in the Central Marriage on KUA Kecamatan Ratu Agung?The type of this research is descriptive research with sociological juridical approach. Data collection using interview technique, observation, documentation. This study concludes that: Firstly, the public welcomes a positive response to the enactment of Government Regulation No. 19 of 2015. The regulation is considered as the government’s new breakthrough to discipline the marriage cost so as to minimize illegal levies. In addition, people with limited economic ability who want to get married is greatly helped by the existence of this provision. If previously the cost of marriage is felt by them is quite high, with this provision they can perform the marriage for free with the condition must be implemented in the Office of Religious Affairs and at work hours. Of course this gets a positive response from the community, because it is very helpful especially for the middle to lower society. Secondly, the factors that cause the community to carry out marriage in the marriage hall at the Office of Religious Affairs of Ratu Agung District are economic factors and work permits. In general, informants stated that getting married in the Office of Religious Affairs without cost so as to ease the financial burden. In ad- dition, the informant was married in the Office of Religious Affairs of Ratu Agung Sub-district due to the reason of the work permit which was not long